Thickness dependence of structure and piezoelectric properties at nanoscale of polycrystalline lead zirconate titanate thin films - Araujo, E. B. (2017)
Lead zirconate titanate Pb(Zr0.50Ti0.50)O-3 (PZT) thin films were deposited by a polymeric chemical method on Pt(111)/Ti/SiO2/Si substrates to understand the mechanisms of phase transformations and the effect of film thickness on the structure, dielectric, and piezoelectric properties in these films. PZT films pyrolyzed at temperatures higher than 350 degrees C present a coexistence of pyrochlore and perovskite phases, while only perovskite phase grows in films pyrolyzed at temperatures lower than 300 degrees C. For pyrochlore-free PZT thin films, a small (100)-orientation tendency near the film-substrate interface was observed. Finally, we demonstrate the existence of a self-polarization effect in the studied PZT thin films. The increase of self-polarization with the film thickness increasing from 200 nm to 710 nm suggests that Schottky barriers and/or mechanical coupling near the film-substrate interface are not primarily responsible for the observed self-polarization effect in our films. (C) 2013 AIP Publishing LLC